The Obama administration and the Israeli-Palestinian conflict. Exploring the ideational and structural factors - Mohamed, Mohamed Mosaad (AUC Knowledge Fountain, 2018)
This study discusses the Obama Administration’s Policy toward the Palestinian- Israeli conflict from 2009 to 2017. It is an attempt to explain the change in the Administration’s approach to the peace process, and the reasons for its inability to achieve a breakthrough in resuming the negotiations between Palestinians and Israelis. Deploying the foreign policy analysis, the study explores the main drivers and outcomes of the American policy concerning the conflict and explains its development over the eight years of Obama’s presidency that started with high expectations on resolving the conflict and ended with prevailing disappointment and fear of the end of the peace process itself.